2011
DOI: 10.1371/journal.pone.0018132
|View full text |Cite
|
Sign up to set email alerts
|

Association of Retinal and Macular Damage with Brain Atrophy in Multiple Sclerosis

Abstract: Neuroaxonal degeneration in the central nervous system contributes substantially to the long term disability in multiple sclerosis (MS) patients. However, in vivo determination and monitoring of neurodegeneration remain difficult. As the widely used MRI-based approaches, including the brain parenchymal fraction (BPF) have some limitations, complementary in vivo measures for neurodegeneration are necessary. Optical coherence tomography (OCT) is a potent tool for the detection of MS-related retinal neurodegenera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
94
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 134 publications
(103 citation statements)
references
References 35 publications
(66 reference statements)
5
94
0
4
Order By: Relevance
“…121 These findings may be explained by the reported correlations between RNFL thickness and brain atrophy. 122,123 Not all studies have found the same, however, others have reported an association between cognitive impairment in MS patients and performance in visual function tests such as low contrast sensitivity testing. 124 Early detection of cognitive dysfunction is important, as cognitive symptoms significantly impact the quality of life in MS patients.…”
Section: Cognitive Impairment In Msmentioning
confidence: 97%
“…121 These findings may be explained by the reported correlations between RNFL thickness and brain atrophy. 122,123 Not all studies have found the same, however, others have reported an association between cognitive impairment in MS patients and performance in visual function tests such as low contrast sensitivity testing. 124 Early detection of cognitive dysfunction is important, as cognitive symptoms significantly impact the quality of life in MS patients.…”
Section: Cognitive Impairment In Msmentioning
confidence: 97%
“…We are familiar with the notion that optic neuritis is more than a demyelination state and that substantial neuroaxonal damage may also occur in the patients, as revealed by recent optical coherence tomography (OCT) studies [15][16][17][18][19] . However, while the functional consequence of this neuroaxonal damage was previously established [20][21][22] , demonstrating reduced visual acuity, contrast acuity and visual quality of life, the functional consequence of demyelination was rarely addressed.…”
Section: The Time-constrained Stereo Protocolmentioning
confidence: 99%
“…Based on these data, the RNFL thickness (RNFLT) and TMV have been proposed as potential surrogate outcome measures of neuro-axonal degeneration in MS [14]. Recent studies suggest that OCT measures of retinal degeneration correlate with MRI measures of brain tissue loss [17][18][19][20][21]. As a limitation of all these studies, time domain OCT (TD-OCT) has been used as opposed to the more advanced and more accurate spectral domain OCT technique (SD-OCT), with faster data acquisition, greater reliability and higher resolution [17,22].…”
Section: Introductionmentioning
confidence: 99%